(untitled) (Research, Society and Development, 2020)
Fairy tales are inserted in the reading formation of each individual in a different way. With regard to their contribution to child development, short stories expand and become an important pillar in the aid of the promotion of the imaginary, construction of self-consciousness, personality and other processes. The present study aimed to understand the potentiality of fairy tales and their contributions in recognized demarcations in childhood, seeking to carry out a qualitative research where this importance and potentiality was expressed, through a bibliographic review contemplating current and classic articles in which the theme was witnessed and could make contributions with the study. The results showed that fairy tales help in the whole process of child development and in the processes that permeate this stage, contributing to the child obtaining greater contribution with regard to imaginative capacity, resilience and taking other roles. It is notorious the imaginary/psychic enrichment that the tales provide the child in the different stages of its development, adapting together with its growth.